DIVERSITY OF ODONATA IN NATURAL AND ARTIFICIAL LAKE HABITATS IN SERANG, BANTEN - Riski Andrian Jasmi; Azeng Nurul Hikmah; Rifan Oktadiansyah; Ammar Miftah Farid; Akhmad Faizal Firdaus (BRIN Publishing (Penerbit BRIN), 2026)
Indonesia is recognized as one of the countries with high biodiversity, including insects from the order Odonata, which consists of dragonflies (Anisoptera) and damselflies (Zygoptera). However, information on Odonata biodiversity in freshwater habitats in the Serang region of Banten Province remains limited. This study aims to describe and analyze Odonata diversity and community structure in two lake habitat types, namely an artificial lake and a natural lake. Sampling was conducted over eight days using an exploratory survey and direct collection method with an insect net, with observations carried out in the morning (08:00-10:00 WIB) and afternoon (15:00-17:00 WIB). Environmental factors measured included temperature, humidity, wind speed, and surrounding vegetation. A total of 10 Odonata species comprising 189 individuals were recorded. The natural lake was strongly dominated by Orthetrum sabina (85.71%), whereas the artificial lake was dominated by Agriocnemis pygmaea (33.61%). The artificial lake showed biodiversity index values of D = 0.241, H′ = 1.644, E = 0.714, and Dmg = 1.883, while the natural lake showed D = 0.7449, H′ = 0.509, E = 0.463, and Dmg = 0.47. These results indicate that the artificial lake has moderate diversity with relatively even species distribution, whereas the natural lake shows strong species dominance and lower diversity. Overall, the artificial lake provides more suitable habitat conditions for supporting Odonata diversity, highlighting the importance of habitat heterogeneity in freshwater ecosystems.